2010
DOI: 10.1097/rli.0b013e3181e07516
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perfusion CT as a Follow-up Modality After Transcatheter Arterial Chemoembolization

Abstract: We believe that perfusion CT is a feasible alternative modality for the successful early response assessment and early detection of a marginally recurred tumor after TACE. However, perfusion CT has limitations for the prediction of tumor recurrence after TACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…However, the role of perfusion CT in predicting recurrence after local-regional treatment is uncertain until now. Indeed, Choi et al (90) reported that for the areas where the recurrence eventually occurred at 4 weeks after TACE, CT perfusion parameters obtained 1 week after TACE did not help predict future recurrence in their study using 14 rabbits the AEF, a value that is similar to HPI. AEF was defined as the ratio of the absolute increase of attenuation during the arterial phase to the absolute increment of attenuation during the portal venous phase: AEF = [(HU A-2HU U )/(HU P 2HU U )] x 100, where HU is the attenuation, A is arterial phase, P is portal phase, and U is unenhanced scan.…”
Section: Monitoring Therapeutic Effectsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the role of perfusion CT in predicting recurrence after local-regional treatment is uncertain until now. Indeed, Choi et al (90) reported that for the areas where the recurrence eventually occurred at 4 weeks after TACE, CT perfusion parameters obtained 1 week after TACE did not help predict future recurrence in their study using 14 rabbits the AEF, a value that is similar to HPI. AEF was defined as the ratio of the absolute increase of attenuation during the arterial phase to the absolute increment of attenuation during the portal venous phase: AEF = [(HU A-2HU U )/(HU P 2HU U )] x 100, where HU is the attenuation, A is arterial phase, P is portal phase, and U is unenhanced scan.…”
Section: Monitoring Therapeutic Effectsmentioning
confidence: 91%
“…Although there were some discrepancies among studies, there was a trend toward showing a decrease in blood flow, blood volume, HPI, and permeability, as well as an increase of MTT after treatment regardless of the imaging modality used (CT vs MR imaging), the therapeutic agent administered (standard chemotherapeutics vs antiangiogenic agents), type of liver tumors imaged (primary vs metastatic liver lesions), and the subject studied (human vs different animal models) (Figs 7, 8). For instance, Ren et al (86) recently showed the usefulness of CT perfusion for early response assessment following anticancer treatment in 100 mice with human colon cancer radiology.rsna.org n Radiology: Volume 272: Number 2-August 2014 also observed 1 week after TACE in another study with 14 rabbit VX2 liver tumors (90). In patients with HCC, Yang et al (91) demonstrated a significant decrease in HAP and HPI in HCCs at 4 weeks after TACE.…”
Section: Monitoring Therapeutic Effectsmentioning
confidence: 96%
“…12,13 In this study, 3 weeks after tumour implantation, the TR showed an abundance of blood vessels, and 30-50% of the centre of the tumour was necrotic, which may have been due to a lack of nutrition. The four increased perfusion parameters of CT (BF, BV, PS and HAF) in the rim of the tumour revealed a high amount of perfusion in the tumour region, suggesting an abundance of blood vessels.…”
mentioning
confidence: 49%
“…The following parameters were used: 2461.2 mm detector configuration, a rotation time of 0.33 s, a cycle time of 1.5 s, coverage of 114 mm, 80 kVp and 100 mAs. 4 ml of non-ionic contrast material (iopromide; Ultravist 370; Bayer Schering Pharma, Berlin, Germany) was injected with a power injector (Medrad, Pittsburgh, PA) at a rate of 1 ml s 21 through a 22-gauge intravenous catheter inserted into the auricular vein [15,16]. Scanning was initiated 5 s after beginning the injection and continued for 96 s. Therefore, 64 contiguous sections were obtained at 1.5 s intervals.…”
Section: Radiological Studymentioning
confidence: 99%